2004
DOI: 10.1090/s0894-0347-04-00464-3
|View full text |Cite
|
Sign up to set email alerts
|

The threshold for random 𝑘-SAT is 2^{𝑘}log2-𝑂(𝑘)

Abstract: Let F k ( n , m ) F_k(n,m) be a random k k -CNF formula formed by selecting uniformly and independently m m out of all possible k k -clauses on n n variables. It is well known that if r ≥ 2 k log ⁡ 2 r \geq 2^k \log 2 , then F k ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…With help of the cavity method, we are able to conjecture improved lower bounds for the satisfiability of QSAT on regular and Erdős-Rényi random graphs, canonical models for quantum constraint optimization problems. These statement hold just as well for classical satisfiabilitybut for some of these classical models better bounds are known [12,13].…”
mentioning
confidence: 86%
“…With help of the cavity method, we are able to conjecture improved lower bounds for the satisfiability of QSAT on regular and Erdős-Rényi random graphs, canonical models for quantum constraint optimization problems. These statement hold just as well for classical satisfiabilitybut for some of these classical models better bounds are known [12,13].…”
mentioning
confidence: 86%
“…On this scale the SAT/UNSAT phase transition occurs at α s = log 2 + O(2 −k ) [6,12]. We shall therefore assume α ∈ (0, log 2).…”
Section: B Intermediate Regimementioning
confidence: 99%
“…The best upper bounds were derived using first moment methods [12,13]. Lower bounds can be found by analyzing some algorithms which find SAT assignments [14,15], but recently a new method, based on second moment methods, has found better and algorithm-independent lower bounds [16,17]. Using these bounds, it was shown that α c (K) scales as 2 K ln(2) when K → ∞.…”
mentioning
confidence: 99%